2010
DOI: 10.4103/0971-9784.62934
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetic management for surgical repair of Ebstein′s anomaly along with coexistent Wolff-Parkinson-White syndrome in a patient with severe mitral stenosis

Abstract: Ebstein's anomaly (EA) is the most common cause of congenital tricuspid regurgitation. The associated anomalies commonly seen are atrial septal defect or patent foramen ovale and accessory conduction pathways. Its association with coexisting mitral stenosis (MS) has uncommonly been described. The hemodynamic consequences and anesthetic implications, of a combination of EA and rheumatic MS, have not so far been discussed in the literature. We report successful anesthetic management of a repair of EA and mitral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Conversely, Dobkowski and colleagues suggested that enflurane may trigger arrhythmias and should not be used in WPW syndrome [30]. In a more recent report, isoflurane was preferred among other volatiles due to its property to prolong the AP refractory period and decrease the likelihood of tachycardias [50]. Similarly, most investigators consider isoflurane as a safe choice for patients with WPW [45,[51][52][53].…”
Section: Anaesthesia For Non-ablative Surgical Proceduresmentioning
confidence: 99%
See 3 more Smart Citations
“…Conversely, Dobkowski and colleagues suggested that enflurane may trigger arrhythmias and should not be used in WPW syndrome [30]. In a more recent report, isoflurane was preferred among other volatiles due to its property to prolong the AP refractory period and decrease the likelihood of tachycardias [50]. Similarly, most investigators consider isoflurane as a safe choice for patients with WPW [45,[51][52][53].…”
Section: Anaesthesia For Non-ablative Surgical Proceduresmentioning
confidence: 99%
“…Among intravenous anaesthetics, propofol does not affect the AP refractory period [22]. Induction or maintenance of anaesthesia with propofol combined with fentanyl has been associated with cardiovascular stability in WPW patients [44,50,54,55,[58][59][60][61][62][63]. Moreover, it was reported that delta waves disappeared after propofol administration and reappeared after its discontinuation [58].…”
Section: Anaesthesia For Non-ablative Surgical Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…[4] Tachyarrythmic sudden death is a threat regardless of the severity of Ebstein's anomaly. [5] There are three case reports in the literature which describes different anaesthetic techniques used for caesarean section in a patient with Ebstein's anomaly.…”
mentioning
confidence: 99%